Self-perceived impact of stroke: A longitudinal comparison between one and five years post-stroke - Erik Skoglund; Emma Westerlind; Hanna C. Persson; Katharina S. Sunnerhagen (Medical Journals Sweden, 2019)
Objective: To investigate different aspects of self-perceived impact of stroke 1 and 5 years after stroke onset, with a focus on self-perceived participation. Design: Longitudinal cohort study. Participants: Forty-five persons diagnosed with first-time stroke included in the Stroke Arm Longitudinal study at University of Gothenburg (SALGOT). Methods: Participants responded to the Stroke Impact Scale, the Impact on Participation and Autonomy and the European Quality of Life 5 dimensions at 1 year and 5 years post-stroke. Wilcoxon signed-rank test was used to check for differences in changes over time between groups. Results: In general, the perceived consequences of stroke were more severe after 5 years compared with at 1 year. Strength, emotion and participation were the areas most affected, along with restrictions in social life and autonomy indoors. Global disability (mRS) was moderately correlated with quality of life. Conclusion: The perceived impact of stroke becomes more prominent with time, even for persons with mild-to-moderate stroke. This study highlights the need for long-term support for persons with stroke.